Anthropocene, History and Politics. Challenges and Critical Itineraries - Furio Ferraresi (Scienza & Politica)
The essay addresses some questions that the concept of the Anthropocene poses not only to political theory but also to the humanities and social sciences. Along a critical itinerary among different theories and authors (from Chakrabarty to Latour, from Moore and Malm to ecofeminism), the essay discusses the concept of the Anthropocene with a ‘political ecology’ approach. The aim is to hold together the common dimension - human and non-human - of belonging to terrestrial eco-systems, with the ability to critically and genealogically read the power asymmetries, inequalities and conflicts that have made possible and still structure the Anthropocene, from the political perspective of inter-human and multi-species climate justice.